Novel antifungal activity of oligostyrylbenzenes compounds on Q5 Candida tropicalis biofilms - Quinteros, Melisa de Los Ángeles (2020)
As sessile cells of fungal biofilms are at least 500-fold more resistant to antifungal drugs than their planktonic counterparts, there is a requirement for new antifungal agents. Olygostyrylbenzenes (OSBs) are the first generation of poly(phenylene) vinylene dendrimers with a gram-positive antibacterial activity. Thus, this study aimed to investigate the antifungal activity of four OSBs (1, 2, 3, and 4) on planktonic cells and biofilms of Candida tropicalis. The minimum inhibitory concentration (MIC) for the planktonic population and the sessileminimum inhibitory concentrations (SMIC) were determined. Biofilm eradication was studied by crystal violet stain and light microscopy (LM), and confocal laser scanning microscopy (CLSM) was also utilized in conjunction with the image analysis software COMSTAT. Although all the OSBs studied had antifungalactivity, the cationic OSBs weremore effective than the anionic ones. A significant reduction of biofilms was observed at MIC and supraMIC50 (50 times higher than MIC) for compound 2, and at supraMIC50 with compound 3. Alterations in surface topography and the three-dimensional architecture of the biofilms were evident with LM and CLSM. The LM analysis revealed that the C. tropicalis strain produced a striking biofilmwith oval blastospores, pseudohyphae, and true hyphae. CLSM images showed that a decrease occurred in the thickness of the mature biofilms treated with the OSBs at the most effective concentration for each one. The results obtained by microscopy were supported by those of the COMSTAT program. Our results revealed an antibiofilm activity, with compound 2 being a potential candidate for the treatment of C. tropicalis infections.